2018
DOI: 10.5650/jos.ess18043
|View full text |Cite
|
Sign up to set email alerts
|

Dietary <i>Sparassis crispa</i> Reduces Body Fat Mass and Hepatic Lipid Levels by Enhancing Energy Expenditure and Suppressing Lipogenesis in Rats

Abstract: Accumulation of abdominal fat triggers metabolic syndrome, which is a cluster of metabolic abnormalities, such as dyslipidemia, glucose intolerance, insulin resistance or hyperinsulinemia, and hypertension, that leads to the development of diabetes and cardiovascular disease. Mushrooms have been used as a foodstuff and folk medicine worldwide. Among these mushrooms, Sparassis crispa (SC) is a relatively newly cultivated edible and medicinal mushroom, which has been reported to have anti-diabetic and anti-hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Of note, previous research has reported reduced hepatic enzyme activities of G6PD and ME in diet‐induced obese rats in response to the addition of Sparassis mushrooms to their diets which was partially responsible for the decrease in hepatic lipid levels of these rats. [ 66 ] Further, hepatic enzyme activity of ME was also reported to be significantly reduced in Mukitake‐fed db/db mice. [ 67 ] Alleviation of hepatosteatosis in obese Zucker rats by PSC may partially be attributed to the suppressed fatty acid synthesis in these rats.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, previous research has reported reduced hepatic enzyme activities of G6PD and ME in diet‐induced obese rats in response to the addition of Sparassis mushrooms to their diets which was partially responsible for the decrease in hepatic lipid levels of these rats. [ 66 ] Further, hepatic enzyme activity of ME was also reported to be significantly reduced in Mukitake‐fed db/db mice. [ 67 ] Alleviation of hepatosteatosis in obese Zucker rats by PSC may partially be attributed to the suppressed fatty acid synthesis in these rats.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-obesity effect of S. crispa has been published using high-fat diet rats, and the related ingredients of S. crispa have been suggested in more than 30 different materials, including polysaccharides ( Takeyama et al, 2018 ; Sharma et al, 2022 ). In another previously reported article, trehalose, which is the ingredient of some mushrooms, has an anti-obesity effect ( Arai et al, 2013 ), and ITSc also has disaccharides, particularly trehalose ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…crispa on fat gain, Takeyama et al reported that S . crispa suppressed body fat mass and triglyceride and cholesterol content in the liver in a study using a high-fat diet-induced male obesity rat model ( Takeyama et al, 2018 ). However, unlike dietary habit-induced obesity, fat gain induced by menopause in women has been reported to be due to abnormal fat metabolism caused by fluctuations in female hormone balance (Tara M D'Eon et al, 2005; Marchand et al, 2018 ), although S .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dyslipidemia, hyperglycemia, hypertension, hypercholesterolemia and abdominal obesity are characterized by a cluster of interdependent disorders (Mohammadbeigi et al, 2018), triggering a collection of metabolic abnormalities (Takeyama et al, 2018), such as heart disease, thrombosis, vasomotor dysfunction in microvessels, mitochondrial function disorder, diabetic nephropathy and renal interstitial fibrosis (Rahmatallah et al, 2017) (Hye Khan et al, 2018). In a recent study, Lee et al identified an overexpression of metabolic disease related-gene related to the upregulation of the inflammatory-related factors interleukin (IL)-6 and tumor necrosis factor (TNF)alpha (Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%